Descrição de desenvolvimento linguístico em língua inglesa por seis surdos : novos olhares sobre o processo de aquisição de uma língua - Moraes, Antonio Henrique Coutelo de (2012)
The inclusive movement brought the language teaching for the deaf new possibilities in the acquisition of first, second and foreign language. We know that the main proposal for the deaf in Brazil maintains a bilingual perspective which brings it to Libras as a first language and Portuguese as a second. Although the acquisition of a foreign language (FL) by the deaf may seem a question that can be postponed as other issues related to second language acquisition have not yet been resolved, we believe in the need to move forward in further discussions. Thereunto, we made this research without, however, failing to be attentive to the context of knowledge acquisition in the deaf school. Thus, this work constitutes a record of our research which had as the principal objective to investigate the possibility of English fluency in six deaf subjects, making it crucial to observe the process of acquisition and learning of FL in an inclusive multi(bi)linguistic educational context. In this context, the theoretical section brings the discussions concerning deafness and second language acquisition and the deaf in the process of teaching and learning of English. The methodology used was the qualitative research. We chose this approach because we believe it allows a better description of the communicative linguistic events in English language by the subjects. Through the results we were able to identify improvement in fluency in English by the deaf, a fact which seems quite encouraging on the belief that learning is not yet offered great expectations. We hope thereby to contribute to this line of research to be expanded, since there have been few initiatives on the subject in our country so far